Real-Time Data Analytics in the Cloud: Enabling Enterprise Decision-Making - Prithvi Raju Rudraraju, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Real-time data analytics in cloud environments represents a transformative shift in how enterprises process and utilize their data streams. This comprehensive article explores cloud-based analytics systems' fundamental components, implementation strategies, and performance considerations. The article examines data ingestion patterns, processing layer optimizations, storage solutions, security mechanisms, and monitoring approaches. Through a detailed examination of event-driven architectures, compliance requirements, and observability patterns, this article provides insights into building robust and efficient real-time analytics systems while maintaining security and regulatory compliance. The article encompasses technical implementation details and business impact considerations, offering a holistic view of modern analytics infrastructure.
Keywords: Real-time Analytics; Cloud Computing; Event-driven Architecture; System Performance; Compliance Monitoring